Answers

2014-12-06T21:56:20+05:30
 let age of father be x
  age of son be y
given x - 2 = 3y - 2
     x-3y = 0 -------- (1)
2(x+2) = 5(y+2)
2x+2 = 5y+10
2x-5y-8 = 0 --------- (2)
(1)×2 ⇒ 2x - 6y = 0
(2)    ⇒ 2x - 5y = 8
-------------------------------
               -y = -8
               y = 8
age of son is 8yrs
sub y = 8 in (1)
x - 3(8) = 0
x = 24
age of father is 24 yrs
age of son is 8yrs.

0
the ans vl nt...
but we haven't studied in two ariables
ok i'll try....
please
WRONG ANSWER
The Brainliest Answer!
2014-12-06T22:21:33+05:30
Let age of son be x
father's age  two yeas back was  3(x-2) and now is 3(x-2)+2
Fathers age  two years hence = 5(x+2)/2 and now is 5(x+2) -2
  Hence            3x-6+2=((5x+10)/2) -2
                       ⇒ 6x - 8=5x+10-4
                       ⇒ x=14
son's age is 14  and fathers age is 38
2 5 2
MARK AS THE BEST....................
ok